Self Regulated Learning di Masa Pandemi Covid-19 Terhadap Motivasi Belajar Siswa Pada Pelajaran Pendidikan Agama Islam (PAI) SMA di Provinsi Banten - Rahmatullah, Mamat; Basrowi, Basrowi (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The COVID-19 pandemic has changed the virtual (online) learning system so that students are expected to remain motivated or motivated to learn. With the motivation to learn, it is expected that students will be interested in learning. Things that are considered to be able to affect students' learning motivation are self-regulated learning. The purpose of this study was to determine the effect of self-regulated learning on high school students in Banten Province. The results showed that self-regulated learning positively affected students' learning motivation in Islamic Religious Education (PAI). So self-regulated learning is essential in the learning process because it can affect learning motivation.